Testing nanoeffect onto model bacteria: Impact of speciation and genotypes. Issue 2 (7th February 2016) - Gelabert, Alexandre; Sivry, Yann; Gobbi, Paola; Mansouri-Guilani, Nina; Menguy, Nicolas; Brayner, Roberta; Siron, Valerie; Benedetti, Marc Fabien; Ferrari, Roselyne
Abstract: The gram-negative bacteria Escherichia coli ( E. coli ) is a very useful prokaryotic model for testing the toxicity of ZnO nanoparticles (nano-ZnO). This toxicity is often linked to Zn 2+ released from nanoparticles in the culture medium, and nano-ZnO dissolution in different media is clearly established. Here, two model E. coli strains MG1655 and W3110 both descendant from the original K-12 showing slight differences in their genome were submitted to nano-ZnO or Zn 2+ in order 1 > to refine the nano-ZnO toxicity mechanisms to E. coli, and 2 > to investigate whether toxicity resulted from a real "nanoparticle" effect or from the release of Zn 2+ in solution. To do so, both strains were submitted to various concentrations (i.e., 0.1–1 mM) of nano-ZnO or Zn 2+ in Luria Bertani (LB) medium. These toxicity studies take into account the nano-ZnO solubility in the culture medium by specifically monitoring the Zn 2+ release in our experimental systems. In our experimental conditions, differences in tolerance to nano-ZnO or Zn 2+ between both strains were clearly evidenced. W3110 is generally more tolerant to metal than MG1655, the latter showing no real difference in its sensitivity to the two zinc added forms unlike W3110. The differences in behavior between both strains could be attributed to differences in the two genomes as a mutation named "amber" in W3110. Moreover, by using these two closely E. coli strains, a real "nano" effect is here clearly demonstrated providing a model to study the toxicity of ZnO nanoparticles.